Numerical simulation of flow instability in a circular tube under pulse heating condition. (December 2019) - Guo, Simao; Guo, Yuchuan; Mi, Xiangmiao; Wang, Guanbo; Qian, Dazhi; Hu, Bo
Highlights: The numerical simulation of flow instability under pulse heating condition is executed. Four flow development stages are identified, and three kind of flow oscillation phenomenon are found. The effect of heating power, pulse heating period and duty ratio on coolant flow are analyzed. The flow development stage maps are given in the plane of average power and inlet subcooled temperature. Abstract: Energy systems based on inertial confinement fusion or fusion-fission hybrid reactor generate energy in the form of pulse heating, which may lead to new flow instability phenomenon in the cooling system. In order to make thermal hydraulic design of pulse heating energy system safe and reliable, it is necessary to deeply understand the oscillation characteristics of flow and heat transfer under the pulse heating condition. As for the first stage of this complicated research, the numerical simulation of coolant flow in a circular tube under pulse heating condition is executed in this paper. The oscillation characteristics of flow and heat transfer under different pulse heating conditions are discussed in detail, and the effect of heating power, pulse heating period and duty ratio are studied. Four flow development stages (stage A – stage D) are identified, and three kind of flow oscillation phenomenon are found according to the numerical results with increasing the pulse heating power. The analysis shows that oscillation is mainly caused by pulse heating itself or the combination of pulse heating and density wave oscillation (DWO). Increasing the pulse heating period is beneficial to decrease flow oscillation, and decreasing the duty ratio, the flow oscillation is more obvious. The flow development stage maps are also given in the plane of average power and inlet subcooled temperature. With the increase of period, the stage D appears more easily at lower average power. When the duty ratio decreases, the region of stage C in instability map becomes larger.